2021
DOI: 10.1021/acs.jpcc.1c05639
|View full text |Cite
|
Sign up to set email alerts
|

Type-II Band Alignment Enhances Unassisted Photoelectrochemical Water-Splitting Performance of the BaTiO3/CdS Ferroelectric Heterostructure Photoanode under Solar Light Irradiation

Abstract: Here, we first use CdS nanoparticles to sensitize ferroelectric BaTiO3 nanostructures to construct the BaTiO3/CdS heterostructure photoanodes by a facile hydrothermal method and subsequent successive ionic layer adsorption and reaction. Combining the measurements of the valence band and core-level X-ray photoelectron spectroscopy spectra with energy band calculation, the type-II energy structure established at the BaTiO3 and CdS interface is confirmed. Benefiting from the type-II band alignment of the heterost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…When the deposition times for the CdS layer were above 5, the photocurrent density of the composite film began to decline, suggesting that excessive deposition of CdS NPs was not conducive to the separation and transfer of the photogenerated carriers as demonstrated previously. 51,52 A similar trend can be observed in pure CdS photoelectrode, where the highest photocurrent density was obtained at 5 deposition times (see Fig. 6a).…”
Section: Resultssupporting
confidence: 83%
“…When the deposition times for the CdS layer were above 5, the photocurrent density of the composite film began to decline, suggesting that excessive deposition of CdS NPs was not conducive to the separation and transfer of the photogenerated carriers as demonstrated previously. 51,52 A similar trend can be observed in pure CdS photoelectrode, where the highest photocurrent density was obtained at 5 deposition times (see Fig. 6a).…”
Section: Resultssupporting
confidence: 83%
“…The above-mentioned g-C 3 N 4 and BiOF-based heterojunction results obviously portray the type-II heterojunction charge-transfer mechanism with CB and VB alignment. Therefore, the g-C 3 N 4 /BiOF heterojunction interface electrode material probably possesses the type-II mechanism of PEC water splitting , (Figure ).…”
Section: Resultsmentioning
confidence: 74%
“…In addition to oxide semiconductors, metal sulfide semiconductor, such as CdS [ 50 , 51 , 52 ], Ag 2 S [ 53 ] etc., could enhance the photo-electric conversion by integrating with ferroelectric. Liu et al, reported that BaTiO 3 -CdS hybrid photocatalysts obtained H 2 production rate of 483 µmol∙h −1 ∙g −1 with the 20 wt% CdS loading due to the spontaneous polarization electric field of BaTiO 3 [ 52 ].…”
Section: Recent Advances Of Different Speciesmentioning
confidence: 99%